Dead on target - Beaton, M. C.; Green, R. W. (Novelist) (Beaton, M. C. Agatha Raisin mystery, 2024)
"Beloved New York Times bestseller M. C. Beaton's cranky, crafty Agatha Raisin--the star of her own hit T.V. series--is back on the case again in Dead on Target. A visit to the local village fete for a spot of fun and relaxation turns into a nightmare for Agatha Raisin when she discovers the body of the local landowner in the woods--with an arrow in his chest and trousers round his ankles. Agatha's old adversary, Detective Chief Inspector Wilkes, declares the death a tragic accident, believing the victim has been hit by a stray arrow from an archery demonstration. Agatha is convinced of foul play, however, and is shocked when Wilkes eventually agrees...with her as his prime murder suspect. Determined to clear her name and find the real killer, Agatha launches her own investigation, quickly becoming involved with a family at war, an unscrupulous gangster--and a killer who is determined to make her the next victim..."--